2022
DOI: 10.3389/fnins.2022.1042442
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease (NAFLD) and mental illness: Mechanisms linking mood, metabolism and medicines

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the world and one of the leading indications for liver transplantation. It is one of the many manifestations of insulin resistance and metabolic syndrome as well as an independent risk factor for cardiovascular disease. There is growing evidence linking the incidence of NAFLD with psychiatric illnesses such as schizophrenia, bipolar disorder and depression mechanistically via genetic, metabolic, inflammatory and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 316 publications
(387 reference statements)
0
10
0
Order By: Relevance
“…The animal behavior tests we conducted showed that the experimental mice were more inclined to explore novel and unprotected areas, suggesting that they were less anxious and more motivated than the control mice. Although it appears that impaired hepatic lipid metabolism significantly affects psychiatric disorders [13][14][15] , the underlying mechanisms remains poorly understood. Our results suggests that liver-innervating vagal sensory neurons may play an important role in developing psychiatric disorders in patients with obesity and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The animal behavior tests we conducted showed that the experimental mice were more inclined to explore novel and unprotected areas, suggesting that they were less anxious and more motivated than the control mice. Although it appears that impaired hepatic lipid metabolism significantly affects psychiatric disorders [13][14][15] , the underlying mechanisms remains poorly understood. Our results suggests that liver-innervating vagal sensory neurons may play an important role in developing psychiatric disorders in patients with obesity and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…We used AAVrg-Cre (Addgene 55636-AAVrg, titer; 2.2 x10 13 pfu/ml), AAVrg-FLEX-GFP (Addgene 51502-AAVrg, titer; 2.3 x10 13 pfu/ml), AAVrg-FLEX-jGCamp7s (Addgene 104491, titer; 2.5 x10 13 pfu/ml). Avil CreERT2 mice received a total volume of 20 ul of viral injection into the medial and left lobes of the livers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] The synergistic effect of obesity and insulin resistance leads to chronic inflammation and impaired fibrinolysis, putting the body in a thrombotic state and becoming an independent risk factor for portal vein thrombosis in liver transplant patients. [38] Many countries, led by the United States, mainly treat metabolic diseases such as obesity and diabetes by improving patients lifestyles, drugs, surgery, or endoscopy to prevent PVT in NAFLD transplant patients. [37] A high-protein, low-calorie diet, and long-term moderate-intensity physical exercise in liver transplant patients can reduce the body quality of patients without compromising the protein storage in liver transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of living standards and the change of diet structure and lifestyle, the incidence of nonalcoholic steatohepatitis (NASH) caused by obesity, hyperlipidemia, and diabetes is gradually increasing. , Some NASH patients even develop liver fibrosis and cirrhosis, which can lead to serious consequences. NASH is a key stage in the disease spectrum of nonalcoholic fatty liver disease (NAFLD), which is the necessary process for the development of simple fatty liver into fatty liver fibrosis and cirrhosis . At present, the pathological mechanism of NASH has not been clarified, and there is a lack of specific clinical treatment methods.…”
Section: Introductionmentioning
confidence: 99%